Airway Nitric Oxide in Children with HDM-Induced Allergic Rhinitis. Issue 3 (May 2022) - Sutiratanachai, Woralak; Kanchongkittiphon, Watcharoot; Klangkalya, Natchanun; Jotikasthira, Wanlapa; Kiewngam, Potjanee; Manuyakorn, Wiparat
Background: Rhinitis is a common problem in children. Airway nitric oxide (NO) was proposed to represent eosinophilic inflammation. Objectives: To evaluate airway NO level in children with house dust mite (HDM)-induced allergic rhinitis Methods: Children aged 5 to 18 years old with moderate–severe persistent rhinitis and positive result for the HDM nasal provocation test (NPT) was enrolled. The nasal symptoms evaluated by total nasal symptom score (TNSS) and visual analog scale (VAS) were recorded. Skin prick test (SPT) to common aeroallergens, fractional exhaled nitric oxide (FeNO), nasal nitric oxide (nNO), and blood test for specific IgE (sIgE) to HDM was measured. Rhinitis severity was categorized as severe if the VAS score > 7. Results: Forty-eight children with HDM-induced allergic rhinitis with the mean age of 9.3 ± 2.4 years were enrolled. nNO levels and VAS score were significantly correlated (R = 0.398, P  = .005). Children with severe rhinitis had significantly higher nNO levels than moderate rhinitis (1652.05 vs 941.30 parts per billion [ppb], P  = .002), while there was no difference in FeNO level. ROC curve analysis demonstrated the cut-off value of nNO at 1350 ppb (AUC 0.764, 95% CI: 0.616-0.911, P  = .002) for detecting severe HDM-induced allergic rhinitis with the sensitivity of 78% and the specificity of 71%. The level of FeNO in children who had HDM mean wheal diameter (MWD) > 8 mm was significantly higher than those with HDM MWD of 3 to 8 mm and those with a negative test (39.7 vs 14.3 vs 14.4 ppb; P  = .006, respectively). Children who had sIgE to HDM < 0.35 KUA/L had significantly lower FeNO than those with sIgE to HDM 0.35 to 50 KUA/L and >50 KUA/L (9.5 vs 19.7 vs 40.4 ppb; P  = .029, respectively). Conclusions: Cut-off value for the diagnosis of severe HDM-induced chronic rhinitis was proposed. Rhinitis children who had a higher degree of HDM sensitization had a higher level of FeNO.